2012
DOI: 10.1007/s00590-012-1093-x
|View full text |Cite
|
Sign up to set email alerts
|

Scapholunate dissociation associated with distal radius fractures

Abstract: Severity of the distal radius fractures is not associated with SLD. Intra-articular fractures were associated with significant increase in the prevalence of SLD. In some cases, SLD may appear after reduction in distal radius. Most cases with SLD are symptomatic, and this may be the reason of poor cases following distal radius fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
11
1
4
Order By: Relevance
“…42 None of these patients received treatment of their ligamentous injury. At final follow-up, 79 patients had tenderness to palpation over the scapholunate interval with fair to poor outcomes on the Green and O'Brien rating system.…”
Section: Clinical Resultsmentioning
confidence: 98%
“…42 None of these patients received treatment of their ligamentous injury. At final follow-up, 79 patients had tenderness to palpation over the scapholunate interval with fair to poor outcomes on the Green and O'Brien rating system.…”
Section: Clinical Resultsmentioning
confidence: 98%
“…Studies have shown that failing to treat SL dissociation in patients with distal radius fracture leads to worse outcomes both clinically and radiographically. 56,58,59,61,62 Appropriate treatment, however, can provide good results. Peicha and colleagues 71 in 1999 performed arthroscopicassisted K-wire fixation of Geissler grade 3 and 4 SL injuries with distal radius fracture with predominantly excellent or good results in patients at an average of 3 years of follow-up.…”
Section: Special Case Scenario: Open Treatment Of Acute Scapholunate mentioning
confidence: 95%
“…[50][51][52][53][54][55][56] Rates when diagnosed radiographically range from 13.3% to 29%. [57][58][59][60][61][62] Mudgal and Hastings suggest the mechanism of this combined injury can be attributed to a combination of tensile stress in ulnar deviation and axial (compression) stress in either radial or ulnar deviation. 63,64 Overall, intra-articular fractures are associated with higher rates of SL injury but SL injury can be found in extra-articular fractures as well.…”
Section: Special Case Scenario: Open Treatment Of Acute Scapholunate mentioning
confidence: 99%
See 1 more Smart Citation
“…Various traumas concomitantly occur around the carpal bones with distal radius fractures (DRF) [ [1] , [2] , [3] ], but some traumas may be overlooked on examination by plain radiography alone [ 2 ]. DRF are common traumas, examined not only by hand surgeons but also orthopedists.…”
Section: Introductionmentioning
confidence: 99%